PENGARUH KEMAMPUAN TEKNIK PEMAKAI, EFEKTIVITAS SISTEM INFORMASI AKUNTANSI, DAN KESESUAAN TUGAS TEKNOLOGI TERHADAP KINERJA INDIVIDU PADA ORGANISASI PERANGKAT DAERAH (OPD) PEMERINTAH PROVINSI MALUKU - Tirza Oktovianti Lenggono; Senda Yunita Leatemia; Trisye Natalia Kilay (Soso-Q : Jurnal Manajemen, 2021)
Abstract This study aims to determine the effect of the user’s technical ability, the effectiveness of accounting information systems, and the suitability of technology tasks on individual performance in the Regional Apparatus Organization of the Maluku Provincial Government. This study uses a purposive sampling technique, where the sample taken is a sample that has the criteria determined by the researcher, namely employees who work in the accounting and finance divisions who use information technology. This results of this study partially show that the technical ability of the user, the effectiveness of accounting information systems, and the suitability of technology tasks affect individual performance in the Regional Apparatus Organization of the Maluku Provincial Government. Keywords: User’s Technical Ability, Effectiveness of Accounting Information Systems, Suitability of Technology Tasks, and Individual Performance.